Research on on-line assembly and calibration system based on laser scanning and optical fiber sensor - Ding, Weijie; Li, Meixuan; Liang, Fang; Gao, Yan; Qin, Wei; Zhang, Hong (Frontiers in Physics, 2023)
In order to improve the degree of assembly automation, an online assembly calibration system based on laser scanning and optical fiber sensor was designed. The optical fiber sensing module is used to obtain the stress field information, and the laser scanning module is used to obtain the point cloud information of the assembly structure. The position offset caused by the stress field is compensated to the 3D point cloud for improving the target reconstruction accuracy. It consists of laser scanning module, optical fiber sensor module, demodulator, data analysis module, etc. Analyzing the structural characteristics of the module, the stress field distribution of the module structure is obtained through simulation analysis, and an appropriate optical fiber sensor network layout is constructed. The stress field distribution of the assembly structure is simulated and analyzed when the force is applied in different directions. The results show that the magnitude and direction of the residual stress have an impact on the distribution of the stress field. At the same time, the stress field diffusion degree under different strength conditions has been also analyzed. In the calibration test of FBG sensor, the functional relationship between wavelength variation and stress is about 0.0011nm/N. The stress test trends of different FBGs were obtained, and the relative error was concentrated between 4.0% and 9.0%, which had good stability. The optical fiber sensor correction parameters are used for 3D points cloud data reconstruction. Compared with the digital and analog point information, test deviation is smaller.